Cathepsin L of the sea cucumber Apostichopus japonicus-molecular characterization and transcriptional response to Vibrio splendidus infection. (February 2016) - Yang, Jingwen; Liu, Huihui; Zheng, Gang; Xiang, Xiaowei; Lv, Zhenming; Wang, Tianming
Abstract: Cathepsin L, a lysosomal endopeptidase, has been noted for its involvement in the innate immune response in invertebrates. Here, the cathepsin L cDNA of the sea cucumber Apostichopus japonicus ( Aj CatL) is identified from an EST library and then cloned by the rapid amplification of the cDNA ends (RACE) PCR. The full-length cDNA is 1678 bp long containing an open reading frame (ORF) of 1002 bp, an 80 bp 5′ UTR and a 599 bp 3′ UTR. The cDNA encodes 333 amino acid residues with a predicted molecular mass of 37.07 kDa and a theoretical isoelectric point (pI) of 5.01. The full-length Aj CatL contains three active sites of eukaryotic thiol (cysteine) protease at positions 133–144, 278–288 and 295–314. Analysis of the predicted tertiary structure of prepro-CatL (17–333 aa) and mature-CatL (116–333 aa) reveals that the propeptide region (17–115 aa) blocks access to the substrate-binding cleft. Phylogenetic analysis shows that the Aj CatL is clustered together with two other CatLs from Strongylocentrotus purpuratus . The enzymatic activity of Aj CatL was verified using a substrate hydrolyzing assay with recombinant m Aj CatL. Further analysis of real time-PCR demonstrates that the expression of Aj CatL mRNA is significantly up-regulated in the coelomocytes in cases of infection with the common bacterial pathogen, Vibrio splendidus . This suggests that the Aj CatL is likely to be involved in the immune response. Highlights: The gene sequence and character of Apostichopus japonicus CatL is proposed. The enzymatic activity of Aj CatL is verified using a substrate hydrolyzing assay. Gene expression of Aj CatL response to Vibrio splendidus infection is detected. Involvement of CatL in innate immune response is indicated in A. japonicus .